Job demands-Resources model on employee deviance of emergency services personnel: A proposed framework /Weng Leong Lee & Muhammad Madi Abdullah - Weng, Leong Lee; Abdullah, Muhammad Madi (Universiti Teknologi MARA Cawangan Pahang, 2019)
The purpose of this paper is to propose a framework for understanding the antecedents of employee deviance in emergency services personnel. Emergency services are a labour intensive sectors and their employees are entrusted to protect life and property of victims during emergencies. Their decisions during the emergency situation is critical and able to minimize the post-disaster impacts. Emergency services personnel are normatively exposed traumatic experiences and work pressure during emergencies and these may resulted them to demonstrate negative reactions such as employee deviance. This paper discusses possible antecedents that determine an emergency services personnel’s deviant behaviors and offers a conceptual framework based on Job Demands-Resources Model and the existing literature to explain employee deviance in emergency services.